Cover Picture: Vectorization and Intracellular Distribution of a Two‐Photon‐Absorbing, Near‐Infrared‐Emitting π‐Extended Boranil Dye (ChemPhotoChem 4/2017). Issue 4 (7th April 2017) - Frath, Denis; Didier, Pascal; Mély, Yves; Massue, Julien; Ulrich, Gilles
Abstract : The Front Cover picture shows a three‐dimensional representation of a π‐extended boranil dye and its metaphoric vectorization in water which enables the monitoring of cellular distribution using fluorescence microscopy. More information can be found in the Communication by J. Massue, G. Ulrich and co‐workers onpage 109 in Issue 4, 2017 (DOI:10.1002/cptc.201700012 ).